All night long with a cowboy - Crews, Caitlin (Crews, Caitlin. Kittredge Ranch, 2021)
If you play with fire... One of the most notorious cowboys in Cold River, Jensen Kittredge always has willing women with sweet smiles vying for a place in his bed. So when the prissy high school librarian sidles up to him in the most disreputable bar in town with a scowl on her face, he has no idea what to make of it. Much less the attraction he feels toward the bespectacled creature who wants something from him... but not that. Yet. Someone gets burned... Harriett Barnett doesn't care for dens of iniquity--or the insolent cowboy she certainly shouldn't find attractive. But one of her students needs her help, and if she needs to corral the infamous Jensen to save him, she will. Trouble is, the town's favorite Kittredge brother is a lot more than she bargained for. Harriett's happy little life is orderly and neat, just how she likes it--until Jensen blows it all apart with his particular brand of addictive passion. Can a modern-day schoolmarm really tame the wildest cowboy in town? Or is Harriet headed for a terrible fall?